THE EFFECT OF CURRENT RATIO AND DEBT TO EQUITY RATIO ON NET PROFIT MARGIN (EMPIRICAL STUDY ON COMPANIES IN THE PLASTICS AND PACKAGING SUB-SECTOR FOR THE PERIOD 2021-2023 LISTED ON THE IDX) - Asya Desva Fitrilia; Afrizal Nilwan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Net Profit Margin (NPM) in plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This study uses the multiple linear regression method to test the relationship between independent variables (CR and DER) and dependent variables (NPM). The data used is the annual financial statements of companies listed on the IDX. The results show that the Current Ratio has a significant positive influence on Net Profit Margin, which shows that companies with higher liquidity tend to have better profitability. In contrast, the Debt to Equity Ratio has a significant negative effect on the Net Profit Margin, which indicates that the higher the DER, the lower the company's profitability due to the greater interest expense. These findings provide insights for company management in managing liquidity and capital structure to increase profitability.